An evaluation of a renewal‐mitigation procedure for inappropriate mealtime behavior. Issue 3 (11th February 2021) - Haney, Sarah D.; Piazza, Cathleen C.; Peterson, Kathryn M.; Greer, Brian D.
Abstract : Renewal, the increase in behavior during extinction following context changes, may be particularly concerning during intervention for feeding disorders because context changes are often necessary for intervention generality and maintenance (Podlesnik et al.,  2017). In the current study, we tested for renewal and evaluated a renewal‐mitigation procedure when we transferred intervention from a therapist to a caregiver, from clinic to the home, and changed the foods the feeder presented. We used an ABA arrangement to evaluate the generality of the renewal effect with 7 participants who engaged in inappropriate mealtime behavior. Context A was functional reinforcement. Context B was function‐based extinction during the control and mitigation conditions and our renewal‐mitigation procedure in the mitigation condition. The renewal test was function‐based extinction in Context A. We observed renewal of inappropriate mealtime behavior in 4 of 7 participants, and our renewal‐mitigation procedure was effective for 4 of 4 participants.